Approach to diarrhea in hematopoietic stem cell transplant recipients - Ghanem, Hebah; Sivasubramanian, Geetha; Chandrasekar, Pranatharthi H (Current opinion in infectious diseases, 2025)
Diarrhea is a frequent and diagnostically challenging complication in hematopoietic stem cell transplant (HSCT) recipients, with etiologies ranging from conditioning-related mucosal injury to opportunistic infections. This review highlights the growing role of multiplex PCR-based gastrointestinal diagnostics and presents a transplant phase-specific framework for evaluating infectious diarrhea. The topic is timely given the increasing use of molecular assays and the clinical need for rapid, accurate pathogen identification in immunocompromised patients. Multiplex PCR gastrointestinal panels have improved sensitivity and turnaround time compared to conventional methods, enabling simultaneous detection of bacterial, viral, and protozoal pathogens. These assays have expanded recognition of previously underdiagnosed infections, such as sapovirus and enteroaggregative Escherichia coli, in HSCT recipients. However, limitations include the inability to distinguish colonization from active infection and the exclusion of pathogens such as Strongyloides stercoralis and cytomegalovirus from many panels. Pathogen distribution varies by transplant phase, reinforcing the need for phase-specific diagnostic strategies. Syndromic PCR-based diagnostics have enhanced the evaluation of infectious diarrhea in HSCT recipients. When interpreted in the context of transplant phase, immune status, and clinical presentation, they support timely and targeted management. Additional testing and assessment of noninfectious causes remain essential for accurate diagnosis.